Controlled synthesis of dicalcium phosphate dihydrate (DCPD) from metastable solutions: insights into pathogenic calcification - A. D. Rafeek (Springer, 2021)
Abstract Calcium phosphate (CaP) compounds may occur in the body as abnormal pathogenic phases in addition to their normal occurrence as bones and teeth. Dicalcium phosphate dihydrate (DCPD; CaPO4·2H2O), along with other significant CaP phases, have been observed in pathogenic calcifications such as dental calculi, kidney stones and urinary stones. While other studies have shown that polar amino acids can inhibit the growth of CaPs, these studies have mainly focused on hydroxyapatite (HAp; Ca10(PO4)6(OH)2) formation from highly supersaturated solutions, while their effects on DCPD nucleation and growth from metastable solutions have been less thoroughly explored. By further elucidating the mechanisms of DCPD formation and the influence of amino acids on those mechanisms, insights may be gained into ways that amino acids could be used in treatment and prevention of unwanted calcifications. The current study involved seeded growth of DCPD from metastable solutions at constant pH in the presence of neutral, acidic and phosphorylated amino acid side chains. As a comparison, solutions were also seeded with calcium pyrophosphate (CPP; Ca2P2O7), a known calcium phosphate inhibitor. The results show that polar amino acids inhibit DCPD growth; this likely occurs due to electrostatic interactions between amino acid side groups and charged DCPD surfaces. Phosphoserine had the greatest inhibitory ability of the amino acids tested, with an effect equal to that of CPP. Clustering of DCPD crystals giving rise to a “chrysanthemum-like” morphology was noted with glutamic acid. This study concludes that molecules containing an increased number of polar side groups will enhance the inhibition of DCPD seeded growth from metastable solutions.